Amyloid myopathy presenting with respiratory failure. Issue 2 (February 1992) - Ashe, J; Borel, C O; Hart, G; Humphrey, R L; Derrick, D A; Kuncl, R W
Abstract : Amyloidosis is a rare cause of myopathy. Its prominent or presenting feature may be respiratory failure. Physiological measurement of transdiaphragmatic pressure and biopsy specimens of muscle show the pathological mechanism to be diaphragm weakness due to amyloid infiltration of the diaphragm rather than parenchymal lung involvement. Thus amyloid myopathy even without the typical macroglossia and muscle pseudohypertrophy should be considered as one of the neurological causes of respiratory failure.